Survey - A Part of "Collingwood" or "Corbum" 7th Election District - St. Mary's County, Maryland. 3-7/10 Acres - G. W. Joy, Surveyor for St. Mary's County (1944)
Survey. Mentions R. A. Mattingly, Road to Camp Denges, Cecil F. Gibson, Canoe Creek